Corporate Sustainability Due Diligence and the Reconfiguration of Civil Liability in Global Supply Chains: A Socio-Legal Study Approach - Fitriani Jamaluddin; Muhammad Ashabul Kahfi (Punggawa Law Review, 2026)
The adoption of Directive (EU) 2024/1760 on corporate sustainability due diligence has changed the private-law position of transnational business contracts in global supply chains. This article examines how the CSDDD reshapes civil liability by turning sustainability due diligence into a legally relevant standard for assessing corporate conduct before human rights or environmental harm occurs. Using normative legal research, the article analyzes the Directive, the UN Guiding Principles on Business and Human Rights, the OECD Guidelines for Multinational Enterprises, and recent legal scholarship on mandatory human rights and environmental due diligence. The findings indicate three main points. First, the CSDDD moves corporate civil liability from a predominantly post-harm model toward a preventive model based on knowledge, leverage, risk identification, and reasonable action. Second, transnational business contracts become channels of regulatory transmission. Supplier codes, audit rights, contractual assurances, remediation clauses, reporting duties, and termination provisions carry EU sustainability standards into private relations with suppliers outside the Union. Third, the CSDDD creates a distributive problem inside supply chains. Covered companies may shift compliance costs, audit burdens, and legal risks to suppliers that are not formally subject to the Directive. The article argues that civil liability under the CSDDD should be assessed relationally, by examining knowledge, commercial leverage, contribution to risk, contractual control, and access to remedy. A due diligence regime is legally meaningful only where contracts allocate prevention costs, remediation duties, and evidentiary responsibilities in a fair and workable manner.